Laporan Keuangan Perspektif SIRI - Chairul Iksan Burhanuddin; Fifi Nur Afifah Ibrahim; Burhanuddin Burhanuddin (Owner : Riset dan Jurnal Akuntansi, 2022)
In order to provide information and make choices, financial reports are delivered to relevant parties. However, because there are so many parties interested in the financial accounts, there is a lot of information asymmetry in the process of presenting them. In order for the information to be used as a firm foundation for internal and external parties, a new perspective is required in the process of presenting financial statements. In order to interpret the meaning of the SIRI perspective financial statements, this study used a qualitative method that was supplemented by a literature review. So that a conclusion regarding the presentation of fresh financial statements can be formed. The findings of this study offer a framework for presenting financial statements from four different perspectives: spiritual Integrity, Reso', and ininnawa. With the goal that these four viewpoints will influence the way financial statements are presented. And, in the future, bring benefits to both internal and external parties.